A Simple, Non - Biological Model for Percutaneous Renal Access Training - Karagozlu Akgul, Ahsen; Unal, Dursun; Demirbas, Murat; Oner, Sedat; Ucar, Murat; Akgul, Korhan; Guzelsoy, Muhammet; Aydos, Murat (Urology Journal, 2018)
Purpose: Percutaneous renal puncture (PRP) is one of the most important and critical step of urology, especially while performing percutaneous nephrostomy and percutaneous nephrolithotomy (PCNL). In the learning period of this procedures, there is a need for validated, effective, economical models for such training. This study describes a simple non - biological model for learning PRP. The aim was to determine the effectivity of this model as a training and assessment tool, and to assess its cost relative to other models. Materials and Methods: We designed a training box, made of foam and rubber with two open sides and performed radiopaque pelvicalyceal system maquettes to insert inside it. Experts in PCNL (i.e., > 100 cases) and novices (i.e., pediatric surgeons and urologists without PCNL experience) performed percutaneous renal puncture. Novices performed a pre -test and a post - test (i.e., after 2 hour training). Data recorded were total procedure time, X - ray exposure time, and number of puncture attempts. Experts who performed PRP successfully were asked to rate the model using a questionnaire. Results: Five experts and 21 novices completed the study. Four experts rated the model as an "excellent" (score 5) training and assessment tool; one expert rated these as "very good" (score 4). Comparisons of novices' pre - and post - test median results revealed significant skill acquisition with shorter procedure time, less X - ray exposure, and fewer attempts for successful puncture (all P < .001). Conclusion: This new non - biological training model is an effective training tool that helps learners improve skills in PRP. The model is simple to construct, economical, and highly re-useable compared to others. It provides good visibility and imaging, is portable, and could be used widely in training centres.